Simultaneous Assay of Immunoreactive β-Lipotropin, γ-Lipotropin, and β-Endorphin in Plasma of Normal Human Subjects, Patients with ACTH/Lipotropin Hypersecretory Syndromes, and Patients undergoing Chronic Hemodialysis - Bertagna, Xavier Y. (1981)
We have studied the relative concentrations of the human immunoreactive (IR) peptides γ-lipotropin (hγLPH, [1-58]hβLPH), β-lipotropin (hβLPH), and β-endorphin (hβEND, [61-91]hβLPH) using gel exclusion chromatography together with a specific radio-immunoassay (RIA) for hγLPH and a RIA that (because hβEND is the COOH-terminus of the hβLPH molecule) measures both hβEND and hβLPH on an equimolar basis. In normal subjects, basal plasma IR-hγLPH was often undetectable (<12.5 fmol/ml), but ranged up to 21 fmol/ml, and IR-hβEND/hβLPH was 10.8±0.7 fmol/ml; previous studies by others suggest that most of the IR-hβEND/hβLPH was probably hβLPH. Both IR-hγLPH and IR-hβEND/hβLPH were significantly elevated (P < 0.001) in patients undergoing chronic hemodialysis (101.5±12.7 and 23.8±2.0 fmol/ml, respectively). Their IR-hγLPH coeluted with standard hγLPH as a single peak, and IR-hβEND/hβLPH coeluted with hβLPH; no distinct peak of IR-hβEND was observed. In patients with ACTH/LPH hypersecretion due to Addison's disease, Nelson's syndrome, or ectopic ACTH syndrome, IR-hγLPH and IR-hβEND/hβLPH were both elevated, and IR-hβEND/hβLPH eluted as two peaks, one coeluting with hβLPH and the other with hβEND. The molar concentrations of all three peptides were significantly correlated with one another. The lower concentrations of endogenous IR-hβEND observed may be due in part to its apparent shorter plasma half-life, as estimated in an Addison's patient given a cortisol infusion. The biologic significance of these three peptides in circulating blood is still unknown. The increased levels of hβLPH and hγLPH in plasma of patients with chronic renal failure suggest that the kidney may be an important organ for their metabolism.